KISTI-ACOMS: Article Contribution Management System - Myung-Seok Choi; Jae-Won Park; Hee-Seok Jeong; Mu-Yeong Kang; Sun-Hwa Hahn (Data Science Journal, 2007)
KISTI-ACOMS has been developed as a part of the national project for raising the information society index of academic societies that began in 2001. ACOMS automates almost every activity of academic societies, including membership management, journal processing, conference organization, and e-journal management and provides a search system. ACOMS can be customized easily by the system administrator of an academic society. The electronic databases built by ACOMS are serviced to the users through the KISTI website (http://www.yeskisti.net) along with other journal databases created in a conventional way. KISTI plans to raise the usage ratio of the ACOMS database to deliver society services up to 100% in the future.